THE EFFECT OF THE USE OF QUIZIZZ IN MATHEMATICS LEARNING ON THE UNDERSTANDING OF TWO-VARIABLE LINEAR EQUATION SYSTEM - Elma Batasia Siregar; Freddy Giawa, Hamidah Nasution (Adisam Publisher, 2025)
This study aims to analyze the impact of using the Quizizz application in mathematics education on students' understanding of Linear Equation Systems with Two Variables . The research method employed is an experimental design with pre-test and post-test, involving two groups of tenth-grade students at a junior high school: an experimental group using Quizizz and a control group utilizing conventional teaching methods. Data were collected through written tests and a motivation questionnaire. The results indicate that the experimental group experienced an increase in the average pre-test score from 60 to 85 on the post-test, while the control group only increased from 58 to 72. Statistical analysis using the t-test showed a t-value of 3.75 with a p-value of 0.001, indicating a significant difference between the two groups. Additionally, 85% of students in the experimental group reported that learning with Quizizz was more engaging, and 90% expressed a desire to use the application again in the future. These findings suggest that the use of Quizizz can enhance students' understanding and motivation in mathematics learning. The study concludes that application-based learning technology can contribute to improving educational quality and recommends that more teachers integrate technology into the learning process to achieve better outcomes.